Estimating the economic value of working donkeys in Ethiopia - Girma Birhan Asteraye; Ruth Jobling; Wudu T. Jemberu; Gina Pinchbeck; Theodore J.D. Knight-Jones; Gemma L. Chaters; Jonathan Rushton (Preventive Veterinary Medicine, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Stochastic modelling of burden of livestock diseases on domestic ruminants in Ethiopia - Wudu T. Jemberu; Gemma Chaters; Theodore J.D. Knight-Jones; William Gilbert; Stephen Kwok; Mieghan Bruce; Benjamin Huntington; Jonathan Rushton (Preventive Veterinary Medicine, 2026)

Micro‐Refuges or Ecological Traps: Context‐Dependent Effects of Rock Pools on Intertidal Biodiversity Across Latitudes - Louise B. Firth; Andrea Desiderato; Antony M. Knights; J. David Aguirre; Juan C. Astudillo; Juan C. Azofeifa‐Solano; David T. Bilton; Su Yin Chee; Hartvig C. Christie; Ronaldo A. Christofoletti; Amelia Curd; Katherine A. Dafforn; et al. (Global Ecology and Biogeography, 2026)
Aim We investigated how local‐scale environmental heterogeneity influences biodiversity patterns across broad biogeographic gradients, using intertidal microhabitats as a model system within one of the most environmentally stressful ecosystems on Earth. Location Intertidal habitats at 26 locations (two rocky shore sites per location) across six continents, spanning 98° of latitude (38°S to 60°N). Time Period 2019–2022. Major Taxa Studied Algae, sessile and mobile invertebrates. Methods We compared biodiversity and thermal environments across contrasting microhabitats (rock pools and adjacent emergent rock) along a latitudinal gradient, sampling during environmentally ‘milder’ and ‘harsher’ periods. Biodiversity was quantified using multiple richness metrics (mean, total, unique taxa) and functional diversity. Results Microhabitat differences strongly influenced biodiversity patterns across latitude. Rock pools consistently supported higher taxonomic and functional diversity than emergent rock, irrespective of sampling period, reflecting their ability to buffer thermal extremes, particularly under harsher conditions. Mean species richness exhibited a non‐linear, s‐shaped latitudinal pattern, with lowest values near the equator and higher richness at mid‐latitudes, diverging from classical Latitudinal Diversity Gradient expectations. Biodiversity differences between microhabitats were greatest in temperate regions and diminished at low latitudes, where extreme conditions constrained diversity across habitats. Main Conclusions Local environmental heterogeneity can substantially modify, and in some cases obscure large‐scale biodiversity patterns. By mediating exposure to environmental stress, intertidal microhabitats provide insight into how fine‐scale variability interacts with latitudinal stress gradients to shape biodiversity distributions. Incorporating microhabitat variability into biogeographic frameworks is important for understanding global biodiversity patterns and predicting ecological responses to climate change.

Classification of donkey systems in Ethiopia - Girma Birhan Asteraye; Ruth Jobling; Wudu T. Jemberu; Gina Pinchbeck; Theodore J.D. Knight-Jones; Rob Critchlow; Jonathan Rushton; Gemma L. Chaters (Preventive Veterinary Medicine, 2026)

Assessment of the movement behaviour of dusky kob Argyrosomus japonicus along the coast of South Africa using 39 years of tag-recapture data from a voluntary tagging project - T Knight; M Farthing; A Winkler; BQ Mann; A-R Childs; WM Potts (African Journal of Marine Science, 2025)

Hindsight informs foresight: revisiting millennial forecasts of impacts and status of rocky shores in 2025 - Stephen J. Hawkins; Kathryn A. O'Shaughnessy; George M. Branch; Laura Airoldi; Simon Bray; Paul Brooks; Michael T. Burrows; Juan Carlos Castilla; Tasman P. Crowe; Thomas W. Davies; Louise B. Firth; Keith Hiscock; et al. (Marine Pollution Bulletin, 2025)

Electrophysiological Signatures of Visual Sensations Elicited by Direct Electrical Stimulation - Yan-Yan Li; Bo Zhang; Jing Wang; Yuri B. Saalmann; Mohsen Afrasiabi; Peng-Cheng Lv; Hai-Xiang Wang; Huan-Huan Xiang; Meng-Yang Wang; Guo-Ming Luan; Robert T. Knight; Liang Wang (Neuroscience Bulletin, 2025)

Scaling up eco-engineering: The role of topographic complexity and spatial variability in shaping biodiversity on coastal structures - Charlotte H. Clubley; Antony M. Knights; Jessica Allen; David T. Bilton; Andy Foggo; Mick E. Hanley; James Murphy; Louisa E. Wood; Louise B. Firth (Science of The Total Environment, 2025)

Restricted cirque glaciers in the Wicklow Mountains, Ireland, during the Nahanagan Stadial (Greenland Stadial‐1/Younger Dryas) - Lauren Knight; Clare M. Boston; Harold Lovell; Timothy T. Barrows; Eric A. Colhoun; David Fink; Nicholas C. Pepin (Journal of Quaternary Science, 2025)
In Ireland, the Nahanagan Stadial (NS) was characterised by cirque glacier, plateau icefield and mountain ice cap expansion and is named after the cirque glacier type‐site of Lough Nahanagan in the Wicklow Mountains. This period is broadly equivalent to the Younger Dryas Stadial and Greenland Stadial‐1 (GS‐1: ~12.9–11.7 ka). Here, we provide the first evaluation of the full extent of NS glaciation in the Wicklow Mountains by combining solar radiation modelling, mapping of glacial geomorphology, 10 Be and 26 Al cosmogenic surface exposure dating, 3D glacier reconstructions and analysis of snowblow and avalanching potential. We identify seven sites that hosted cirque glaciers at this time. Glacier extent was very restricted, with most glaciers only partially filling their cirques. Equilibrium line altitudes (ELAs) ranged from 470 ± 5 m a.s.l. (Lough Nahanagan) to 721 ± 5 m a.s.l. (Lough Cleevaun), with an average ELA of 599 m a.s.l. Higher snowblow and avalanching contributions at sites with lower ELAs demonstrate local topoclimatic influence on glacier growth and preservation alongside regional climate. The Wicklow Mountains provides a good example of marginal cirque glaciation during GS‐1 and the importance of local topography and microclimate for sustaining glaciers in some mountain areas of Britain and Ireland.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Multi-generational dispersal and dynamic patch occupancy reveals spatial and temporal stability of seascapes - Charlotte H. Clubley; Tiago A.M. Silva; Louisa E. Wood; Louise B. Firth; David T. Bilton; Enda O'Dea; Antony M. Knights (Science of The Total Environment, 2024)

Experimental constraints on barium isotope fractionation during adsorption–desorption reactions: Implications for weathering and erosion tracer applications - Alasdair C.G. Knight; Edward T. Tipper; Harold J. Bradbury; Alexandra V. Turchyn; Christoff Andermann; Heye Freymuth; Tim Elliott; Luke Bridgestock (Geochimica et Cosmochimica Acta, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Economic losses due to foot-and-mouth disease (FMD) in Ethiopian cattle - P. Rasmussen; A.P. Shaw; W.T. Jemberu; T. Knight-Jones; B. Conrady; O.O. Apenteng; Y. Cheng; V. Muñoz; J. Rushton; P.R. Torgerson (Preventive Veterinary Medicine, 2024)

The impact of adsorption–desorption reactions on the chemistry of Himalayan rivers and the quantification of silicate weathering rates - Alasdair C.G. Knight; Emily I. Stevenson; Luke Bridgestock; J. Jotautas Baronas; William J. Knapp; Basanta Raj Adhikari; Christoff Andermann; Edward T. Tipper (Earth and Planetary Science Letters, 2024)

Navigating diverse commercial fisher perspectives for effective knowledge exchange in fisheries research and management - Rob Hoschke; Natasha Pauli; Tim Langlois; Andrew T. Knight; Harriet Davies; Matt Navarro (Environmental Science & Policy, 2024)

Community Health Navigators for Cancer Screening Among Deaf, Deafblind, and Hard of Hearing Adults Who Use American Sign Language - E. Bergeron; R. Valdez; C. J. Moreland; R. Wang; T. Knight; P. Kushalnagar (Journal of Cancer Education, 2024)
Deaf, deafblind, and hard of hearing (DDBHH) individuals experience barriers to accessing cancer screening, including ineffective patient-physician communication when discussing screening recommendations. For other underserved communities, culturally and linguistically aligned community health navigators (CHNs) have been shown to improve cancer screening and care. A needs assessment study was conducted to identify barriers and gather recommendations for CHN training resources. A community-based participatory needs assessment was conducted from May 2022 to June 2022 using three focus groups. Eight were cancer survivors, six advocates/navigators, and three clinicians. All questions were semi-structured and covered screening barriers, observations or personal experiences, perceived usefulness of having a CHN to promote cancer screening adherence, and training resources that may be useful to American Sign Language (ASL)–proficient CHNs, who are also culturally and linguistically aligned. Out of 20 focus group participants, seven self-identified as persons of color. Data highlighted systemic, attitudinal, communication, and personal-level barriers as recurrent themes. The most frequently cited barrier was access to training that supports the role and competencies of CHNs, followed by cultural considerations, access to cancer guidelines in ASL, dialect diversity in sign language, and the health system itself. Unaddressed barriers can contribute to health disparities, such as lower preventive cancer screening rates amongst DDBHH individuals. The next step is to translate recommendations into actionable tasks for DDBHH CHN training programs. As a result, CHNs will be well-equipped to help DDBHH individuals navigate and overcome their unique barriers to cancer screening and healthcare access.

Priority effects transcend scales and disciplines in biology - J.T. Stroud; B.M. Delory; E.M. Barnes; J.M. Chase; L. De Meester; J. Dieskau; T.N. Grainger; F.W. Halliday; P. Kardol; T.M. Knight; E. Ladouceur; C.J. Little; et al. (Trends in Ecology & Evolution, 2024)

Rationalising development of classification systems describing livestock production systems for disease burden analysis within the Global Burden of Animal Diseases programme - Yin Li; K. Marie McIntyre; Philip Rasmussen; William Gilbert; Gemma Chaters; Kassy Raymond; Wudu T. Jemberu; Andrew Larkins; Grace T. Patterson; Stephen Kwok; Alexander James Kappes; Dianne Mayberry; et al. (Research in Veterinary Science, 2024)

Electrocorticographic Activation Patterns of Electroencephalographic Microstates - Christian A. Mikutta; Robert T. Knight; Daniela Sammler; Thomas J. Müller; Thomas Koenig (Brain Topography, 2024)
Electroencephalography (EEG) microstates are short successive periods of stable scalp field potentials representing spontaneous activation of brain resting-state networks. EEG microstates are assumed to mediate local activity patterns. To test this hypothesis, we correlated momentary global EEG microstate dynamics with the local temporo-spectral evolution of electrocorticography (ECoG) and stereotactic EEG (SEEG) depth electrode recordings. We hypothesized that these correlations involve the gamma band. We also hypothesized that the anatomical locations of these correlations would converge with those of previous studies using either combined functional magnetic resonance imaging (fMRI)-EEG or EEG source localization. We analyzed resting-state data (5 min) of simultaneous noninvasive scalp EEG and invasive ECoG and SEEG recordings of two participants. Data were recorded during the presurgical evaluation of pharmacoresistant epilepsy using subdural and intracranial electrodes. After standard preprocessing, we fitted a set of normative microstate template maps to the scalp EEG data. Using covariance mapping with EEG microstate timelines and ECoG/SEEG temporo-spectral evolutions as inputs, we identified systematic changes in the activation of ECoG/SEEG local field potentials in different frequency bands (theta, alpha, beta, and high-gamma) based on the presence of particular microstate classes. We found significant covariation of ECoG/SEEG spectral amplitudes with microstate timelines in all four frequency bands (p = 0.001, permutation test). The covariance patterns of the ECoG/SEEG electrodes during the different microstates of both participants were similar. To our knowledge, this is the first study to demonstrate distinct activation/deactivation patterns of frequency-domain ECoG local field potentials associated with simultaneous EEG microstates.

Vegetation restoration following dieback of Phragmites australis in the Mississippi River Delta, USA - Herie Lee; Rodrigo Diaz; Joseph Johnston; Ian A. Knight; John A. Nyman; James T. Cronin (Wetlands, 2023)

Epistemology of ignorance: the contribution of philosophy to the science-policy interface of marine biosecurity - Anne Schwenkenbecher; Chad L. Hewitt; Remco Heesen; Marnie L. Campbell; Oliver Fritsch; Andrew T. Knight; Erin Nash (Frontiers in Marine Science, 2023)
Marine ecosystems are under increasing pressure from human activity, yet successful management relies on knowledge. The evidence-based policy (EBP) approach has been promoted on the grounds that it provides greater transparency and consistency by relying on ‘high quality’ information. However, EBP also creates epistemic responsibilities. Decision-making where limited or no empirical evidence exists, such as is often the case in marine systems, creates epistemic obligations for new information acquisition. We argue that philosophical approaches can inform the science-policy interface. Using marine biosecurity examples, we specifically examine the epistemic challenges in the acquisition and acceptance of evidence to inform policy, discussing epistemic due care and biases in consideration of evidence.

Science paper or big data? Assessing invasion dynamics using observational data - Charlotte H. Clubley; Louise B. Firth; Louisa E. Wood; David T. Bilton; Tiago A.M. Silva; Antony M. Knights (Science of The Total Environment, 2023)

Stability and Function of Extracellular Vesicles Derived from Immortalized Human Corneal Stromal Stem Cells: A Proof of Concept Study - Ning Lyu; Robert Knight; Sarah Y. T. Robertson; Aurelie Dos Santos; Chi Zhang; Chao Ma; Jianjiang Xu; Jie Zheng; Sophie X. Deng (The AAPS Journal, 2022)
With significant advancement and development of extracellular vesicle (EV)-based therapies, there is a growing need to understand how their storage affects their physical and functional characteristics. EVs were isolated from the conditioned medium of a corneal stromal stem cell line (imCSSC) using Total Exosome isolation kit (TEI) and ultracentrifugation (UC) combined protocol. Purified EVs were stored at 4°C, − 80°C, room temperature (RT) after lyophilization with or without trehalose for 4 weeks. EVs stored at − 80°C and RT (lyophilization with trehalose) demonstrated a comparable morphology, while the freeze-dried samples without trehalose showed aggregation and degradation under a transmission electron microscope (TEM). Lyophilized samples without trehalose demonstrated a decreased particle concentration, recovery rate and protein concentration, which was remediated by the addition of trehalose. EVs stored at − 80℃ showed no change in the protein expression of CD9, CD63, and CD81. Regardless of the storage condition, all EV samples investigated reduced inflammation, as well as inhibited expression of fibrotic markers in vitro . Lyophilization of EVs with trehalose was a feasible storage method that retained the physical property and in vitro biological activities of EVs after 4 weeks of storage, while − 80°C offered the best retention of imCSSC-derived EV physical properties. For the first time, this data demonstrated a practical and translatable method for the storage of CSSC-derived EVs for clinical use. Graphical Abstract

Allometric patterns in phrynosomatid lizards and the implications for reconstructing body size for fossils - Jaylin A. Knight; David T. Ledesma; Melissa E. Kemp (Evolutionary Ecology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Connecting the food and agriculture sector to nutrition interventions for improved health outcomes - E. Duncan; L. Ashton; A. R. Abdulai; T. Sawadogo-Lewis; S. E. King; E. D. G. Fraser; S. Vosti; J. Haines; F. Knight; T. Roberton (Food Security, 2022)
To achieve the Sustainable Development Goal of zero hunger, multi-sectoral strategies to improve nutrition are necessary. Building towards this goal, the food and agriculture sector must be considered when designing nutritional interventions. Nevertheless, most frameworks designed to guide nutritional interventions do not adequately capture opportunities for integrating nutrition interventions within the food and agriculture sector. This paper aims to highlight how deeply connected the food and agriculture sector is to underlying causes of malnutrition and identify opportunities to better integrate the food and agriculture sector and nutrition in low and middle income countries. In particular, this paper: (1) expands on the UNICEF conceptual framework for undernutrition to integrate the food and agriculture sector and nutrition outcomes, (2) identifies how nutritional outcomes and agriculture are linked in six important ways by defining evidence-based food and agriculture system components within these pathways: as a source of food, as a source of income, through food prices, women’s empowerment, women’s utilization of time, and women’s health and nutritional status, and (3) shows that the food and agriculture sector facilitates interventions through production, processing and consumption, as well as through farmer practices and behavior. Current frameworks used to guide nutrition interventions are designed from a health sector paradigm, leaving agricultural aspects not sufficiently leveraged. This paper concludes by proposing intervention opportunities to rectify the missed opportunities generated by this approach. Program design should consider the ways that the food and agriculture sector is linked to other critical sectors to comprehensively address malnutrition. This framework is designed to help the user to begin to identify intervention sites that may be considered when planning and implementing multi-sectoral nutrition programs.

Evolution of Permeability in Sandstone During Confined Brazilian Testing - T. Hagengruber; M. M. Reda Taha; E. Rougier; E. E. Knight; J. C. Stormont (Rock Mechanics and Rock Engineering, 2022)

Correction to: Extreme longevity variants at the FOXO3 locus may moderate FOXO3 isoform levels - Ryan Frankum; Tom S. O. Jameson; Bridget A. Knight; Francis B. Stephens; Benjamin T. Wall; Timothy A. Donlon; Trevor Torigoe; Bradley J. Willcox; D. Craig Willcox; Richard C. Allsopp; Lorna W. Harries (GeroScience, 2022)

Extreme longevity variants at the FOXO3 locus may moderate FOXO3 isoform levels - Ryan Frankum; Tom S. O. Jameson; Bridget A. Knight; Francis B. Stephens; Benjamin T. Wall; Timothy A. Donlon; Trevor Torigoe; Bradley J. Willcox; D. Craig Willcox; Richard C. Allsopp; Lorna W. Harries (GeroScience, 2022)
The rs2802292, rs2764264 and rs13217795 variants of FOXO3 have been associated with extreme longevity in multiple human populations, but the mechanisms underpinning this remain unclear. We aimed to characterise potential effects of longevity-associated variation on the expression and mRNA processing of the FOXO3 gene. We performed a comprehensive assessment of FOXO3 isoform usage across a wide variety of human tissues and carried out a bioinformatic analysis of the potential for longevity-associated variants to disrupt regulatory regions involved in isoform choice. We then related the expression of full length and 5′ truncated FOXO3 isoforms to rs13217795 genotype in peripheral blood and skeletal muscle from individuals of different rs13217795 genotypes. FOXO3 isoforms displayed considerable tissue specificity. We determined that rs13231195 and its tightly aligned proxy variant rs9400239 may lie in regulatory regions involved in isoform choice. The longevity allele at rs13217795 was associated with increased levels of full length FOXO3 isoforms in peripheral blood and a decrease in truncated FOXO3 isoforms in skeletal muscle RNA. We suggest that the longevity effect of FOXO3 SNPs may in part derive from a shift in isoform usage in skeletal muscle away from the production of 5′ truncated FOXO3 isoforms lacking a complete forkhead DNA binding domain, which may have compromised functionality.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Lock operations influence upstream passages of invasive and native fishes at a Mississippi River high-head dam - Andrea K. Fritts; Brent C. Knights; Jessica C. Stanton; Amanda S. Milde; Jon M. Vallazza; Marybeth K. Brey; Sara J. Tripp; Thomas E. Devine; Wesley Sleeper; James T. Lamer; Kyle J. Mosel (Biological Invasions, 2021)

Investigating Plant Phenotype, Salinity, and Infestation by the Roseau Cane Scale as Factors in the Die-Back of Phragmites australis in the Mississippi River Delta, USA - Ian A. Knight; James T. Cronin; Madeline Gill; John A. Nyman; Blake E. Wilson; Rodrigo Diaz (Wetlands, 2020)

Relationship between conservation biology and ecology shown through machine reading of 32,000 articles - Rogier E. Hintzen; Marina Papadopoulou; Ross Mounce; Cristina Banks‐Leite; Robert D. Holt; Morena Mills; Andrew T. Knight; Armand M. Leroi; James Rosindell (Conservation Biology, 2020)
Conservation biology was founded on the idea that efforts to save nature depend on a scientific understanding of how it works. It sought to apply ecological principles to conservation problems. We investigated whether the relationship between these fields has changed over time through machine reading the full texts of 32,000 research articles published in 16 ecology and conservation biology journals. We examined changes in research topics in both fields and how the fields have evolved from 2000 to 2014. As conservation biology matured, its focus shifted from ecology to social and political aspects of conservation. The 2 fields diverged and now occupy distinct niches in modern science. We hypothesize this pattern resulted from increasing recognition that social, economic, and political factors are critical for successful conservation and possibly from rising skepticism about the relevance of contemporary ecological theory to practical conservation.

Do differences in developmental mode shape the potential for local adaptation? - L. L. Jupe; D. T. Bilton; A. M. Knights (Ecology, 2020)
Future climate change is leading to the redistribution of life on Earth as species struggle to cope with rising temperatures. Local adaptation allows species to become locally optimized and persist despite environmental selection, but the extent to which this occurs in nature may be limited by dispersal and gene flow. Congeneric marine gastropod species ( Littorina littorea and L. saxatilis ) with markedly different developmental modes were collected from across a latitudinal thermal gradient to explore the prevalence of local adaptation to temperature. The acute response of metabolic rate (using oxygen consumption as a proxy) to up‐ramping and down‐ramping temperature regimes between 6°C and 36°C was quantified for five populations of each species. The highly dispersive L. littorea exhibited minimal evidence of local adaptation to the thermal gradient, with no change in thermal optimum ( T opt ) or thermal breadth ( T br ) and a decline in maximal performance ( max ) with increasing latitude. In contrast, the direct developing L. saxatilis displayed evidence of local optimization, although these varied idiosyncratically with latitude, suggesting a suite of selective pressures may be involved in shaping thermal physiology in this relatively sedentary species. Our results show that the biogeography of thermal traits can differ significantly between related species, and show that interpopulation differences in thermal performance do not necessarily follow simple patterns that may be predicted based on latitudinal changes in environmental temperatures. Further research is clearly required to understand the mechanisms that can lead to the emergence of local adaptation in marine systems better and allow improved predictions of species redistribution in response to climate change.

Similar factors underlie tree abundance in forests in native and alien ranges - Masha T. van der Sande; Helge Bruelheide; Wayne Dawson; Jürgen Dengler; Franz Essl; Richard Field; Sylvia Haider; Mark van Kleunen; Holger Kreft; Joern Pagel; Jan Pergl; Oliver Purschke; et al. (Global Ecology and Biogeography, 2020)
Aim Alien plant species can cause severe ecological and economic problems, and therefore attract a lot of research interest in biogeography and related fields. To identify potential future invasive species, we need to better understand the mechanisms underlying the abundances of invasive tree species in their new ranges, and whether these mechanisms differ between their native and alien ranges. Here, we test two hypotheses: that greater relative abundance is promoted by (a) functional difference from locally co‐occurring trees, and (b) higher values than locally co‐occurring trees for traits linked to competitive ability. Location Global. Time period Recent. Major taxa studied Trees. Methods We combined three global plant databases: sPlot vegetation‐plot database, TRY plant trait database and Global Naturalized Alien Flora (GloNAF) database. We used a hierarchical Bayesian linear regression model to assess the factors associated with variation in local abundance, and how these relationships vary between native and alien ranges and depend on species’ traits. Results In both ranges, species reach highest abundance if they are functionally similar to co‐occurring species, yet are taller and have higher seed mass and wood density than co‐occurring species. Main conclusions Our results suggest that light limitation leads to strong environmental and biotic filtering, and that it is advantageous to be taller and have denser wood. The striking similarities in abundance between native and alien ranges imply that information from tree species’ native ranges can be used to predict in which habitats introduced species may become dominant.

Current climate, isolation and history drive global patterns of tree phylogenetic endemism - Brody Sandel; Patrick Weigelt; Holger Kreft; Gunnar Keppel; Masha T. van der Sande; Sam Levin; Stephen Smith; Dylan Craven; Tiffany M. Knight (Global Ecology and Biogeography, 2020)
Aim We mapped global patterns of tree phylogenetic endemism (PE) to identify hotspots and test hypotheses about possible drivers. Specifically, we tested hypotheses related to current climate, geographical characteristics and historical conditions and assessed their relative importance in shaping PE patterns. Location Global. Time period We used the present distribution of trees, and predictors covering conditions from the mid‐Miocene to present. Major taxa studied All seed‐bearing trees. Methods We compiled distributions for 58,542 tree species across 463 regions worldwide, matched these to a recent phylogeny of seed plants and calculated PE for each region. We used a suite of predictor variables describing current climate (e.g., mean annual temperature), geographical characteristics (e.g., isolation) and historical conditions (e.g., tree cover at the Last Glacial Maximum) in a spatial regression model to explain variation in PE. Results Tree PE was highest on islands, and was higher closer to the equator. All three groups of predictor variables contributed substantially to the PE pattern. Isolation and topographic heterogeneity promoted high PE, as did high current tree cover. Among mainland regions, temperature seasonality was strongly negatively related to PE, while mean annual temperature was positively related to PE on islands. Some relationships differed among the major floristic regions. For example, tree cover at the Last Glacial Maximum was a positive predictor of PE in the Palaeotropics, while tree cover at the Miocene was a negative predictor of PE in the Neotropics. Main conclusions Globally, PE can be explained by a combination of geographical, historical and current factors. Some geographical variables appear to be key predictors of PE. However, the impact of historic and current climate variables differs considerably among the major floristic regions, reflecting their unique histories. Hence, the current distribution of trees is the result of globally relevant geographical drivers and regional climatic histories.

Improving conservation practice with principles and tools from systems thinking and evaluation - Andrew T. Knight; Carly N. Cook; Kent H. Redford; Duan Biggs; Claudia Romero; Alejandro Ortega-Argueta; Cameron D. Norman; Beverly Parsons; Martin Reynolds; Glenda Eoyang; Matt Keene (Sustainability Science, 2019)

Identification of Bighead Carp and Silver Carp early-life environments and inferring Lock and Dam 19 passage in the Upper Mississippi River: insights from otolith chemistry - Gregory W. Whitledge; Brent Knights; Jon Vallazza; James Larson; Michael J. Weber; James T. Lamer; Quinton E. Phelps; Jacob D. Norman (Biological Invasions, 2019)

Light social drinkers are more distracted by irrelevant information from an induced attentional bias than heavy social drinkers - Helen C. Knight; Daniel T. Smith; David C. Knight; Amanda Ellison (Psychopharmacology, 2018)

Invasion of Nipponaclerda biwakoensis (Hemiptera: Aclerdidae) and Phragmites australis die-back in southern Louisiana, USA - Ian A. Knight; Blake E. Wilson; Madeline Gill; Leslie Aviles; James T. Cronin; John A. Nyman; Scott A. Schneider; Rodrigo Diaz (Biological Invasions, 2018)

Reflections on, and visions for, the changing field of pollination ecology - T. M. Knight; T.‐L. Ashman; J. M. Bennett; J. H. Burns; S. Passonneau; J. A. Steets (Ecology Letters, 2018)
Since the launch of Ecology Letters in 1998, the field of Pollination Ecology has changed considerably in its focus. In this review, we discuss the major discoveries across the past two decades. We quantitatively synthesise the frequency by which different concepts and topics appeared in the peer‐reviewed literature, as well as the connections between these topics. We then look forward to identify pressing research frontiers and opportunities for additional integration in the future. We find that there has been a shift towards viewing plant–pollinator interactions as networks and towards understanding how global drivers influence the plants, pollinators and the ecosystem service of pollination. Future frontiers include moving towards a macroecological view of plant–pollinator interactions, understanding how ecological intensification and urbanisation will influence pollination, considering other interactions, such as plant–microbe–pollinator networks, and understanding the causes and consequences of extinctions. Pollination Ecology is poised to advance our basic understanding of the ecological and evolutionary factors that shape plant–animal interactions and to create applied knowledge that informs conservation decision making.

Black swans, cognition, and the power of learning from failure - Allison S. Catalano; Kent Redford; Richard Margoluis; Andrew T. Knight (Conservation Biology, 2018)
Failure carries undeniable stigma and is difficult to confront for individuals, teams, and organizations. Disciplines such as commercial and military aviation, medicine, and business have long histories of grappling with it, beginning with the recognition that failure is inevitable in every human endeavor. Although conservation may arguably be more complex, conservation professionals can draw on the research and experience of these other disciplines to institutionalize activities and attitudes that foster learning from failure, whether they are minor setbacks or major disasters. Understanding the role of individual cognitive biases, team psychological safety, and organizational willingness to support critical self‐examination all contribute to creating a cultural shift in conservation to one that is open to the learning opportunity that failure provides. This new approach to managing failure is a necessary next step in the evolution of conservation effectiveness.

The Microbiota, Immunoregulation, and Mental Health: Implications for Public Health - Christopher A. Lowry; David G. Smith; Philip H. Siebler; Dominic Schmidt; Christopher E. Stamper; James E. Hassell; Paula S. Yamashita; James H. Fox; Stefan O. Reber; Lisa A. Brenner; Andrew J. Hoisington; Teodor T. Postolache; et al. (Current Environmental Health Reports, 2016)

Breast cancer survival among young women: a review of the role of modifiable lifestyle factors - Darren R. Brenner; Nigel T. Brockton; Joanne Kotsopoulos; Michelle Cotterchio; Beatrice A. Boucher; Kerry S. Courneya; Julia A. Knight; Ivo A. Olivotto; May Lynn Quan; Christine M. Friedenreich (Cancer Causes & Control, 2016)

Quantifying the relative irreplaceability of important bird and biodiversity areas - Moreno Di Marco; Thomas Brooks; Annabelle Cuttelod; Lincoln D.C. Fishpool; Carlo Rondinini; Robert J. Smith; Leon Bennun; Stuart H.M. Butchart; Simon Ferrier; Ruud P.B. Foppen; Lucas Joppa; Diego Juffe‐Bignoli; et al. (Conservation Biology, 2016)
World governments have committed to increase the global protected areas coverage by 2020, but the effectiveness of this commitment for protecting biodiversity depends on where new protected areas are located. Threshold‐ and complementarity‐based approaches have been independently used to identify important sites for biodiversity. We brought together these approaches by performing a complementarity‐based analysis of irreplaceability in important bird and biodiversity areas (IBAs), which are sites identified using a threshold‐based approach. We determined whether irreplaceability values are higher inside than outside IBAs and whether any observed difference depends on known characteristics of the IBAs. We focused on 3 regions with comprehensive IBA inventories and bird distribution atlases: Australia, southern Africa, and Europe. Irreplaceability values were significantly higher inside than outside IBAs, although differences were much smaller in Europe than elsewhere. Higher irreplaceability values in IBAs were associated with the presence and number of restricted‐range species; number of criteria under which the site was identified; and mean geographic range size of the species for which the site was identified (trigger species). In addition, IBAs were characterized by higher irreplaceability values when using proportional species representation targets, rather than fixed targets. There were broadly comparable results when measuring irreplaceability for trigger species and when considering all bird species, which indicates a good surrogacy effect of the former. Recently, the International Union for Conservation of Nature has convened a consultation to consolidate global standards for the identification of key biodiversity areas (KBAs), building from existing approaches such as IBAs. Our results informed this consultation, and in particular a proposed irreplaceability criterion that will allow the new KBA standard to draw on the strengths of both threshold‐ and complementarity‐based approaches.

The invertebrate ecology of the Chalk aquifer in England (UK) - L. Maurice; A. R. Robertson; D. White; L. Knight; T. Johns; F. Edwards; M. Arietti; J. P. R. Sorensen; D. Weitowitz; B. P. Marchant; J. P. Bloomfield (Hydrogeology Journal, 2016)

Intraspecific variation in Fraxinus pennsylvanica responses to emerald ash borer (Agrilus planipennis) - J. L. Koch; D. W. Carey; M. E. Mason; T. M. Poland; K. S. Knight (New Forests, 2015)

A Multidisciplinary Conceptualization of Conservation Opportunity - KATIE MOON; VANESSA M. ADAMS; STEPHANIE R. JANUCHOWSKI‐HARTLEY; MAKSYM POLYAKOV; MORENA MILLS; DUAN BIGGS; ANDREW T. KNIGHT; EDWARD T. GAME; CHRISTOPHER M. RAYMOND (Conservation Biology, 2014)
An opportunity represents an advantageous combination of circumstances that allows goals to be achieved. We reviewed the nature of opportunity and how it manifests in different subsystems (e.g., biophysical, social, political, economic) as conceptualized in other bodies of literature, including behavior, adoption, entrepreneur, public policy, and resilience literature. We then developed a multidisciplinary conceptualization of conservation opportunity. We identified 3 types of conservation opportunity: potential , actors remove barriers to problem solving by identifying the capabilities within the system that can be manipulated to create support for conservation action; traction , actors identify windows of opportunity that arise from exogenous shocks, events, or changes that remove barriers to solving problems; and existing , everything is in place for conservation action (i.e., no barriers exist) and an actor takes advantage of the existing circumstances to solve problems. Different leverage points characterize each type of opportunity. Thus, unique stages of opportunity identification or creation and exploitation exist: characterizing the system and defining problems; identifying potential solutions; assessing the feasibility of solutions; identifying or creating opportunities; and taking advantage of opportunities. These stages can be undertaken independently or as part of a situational analysis and typically comprise the first stage, but they can also be conducted iteratively throughout a conservation planning process. Four types of entrepreneur can be identified (business, policy, social, and conservation), each possessing attributes that enable them to identify or create opportunities and take advantage of them. We examined how different types of conservation opportunity manifest in a social–ecological system (the Great Barrier Reef) and how they can be taken advantage of. Our multidisciplinary conceptualization of conservation opportunity strengthens and legitimizes the concept.

Clostridium difficile infection diagnosis in a paediatric population: comparison of methodologies - J. Hart; P. Putsathit; D. R. Knight; L. Sammels; T. V. Riley; A. Keil (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Meta‐Analysis of Attitudes toward Damage‐Causing Mammalian Wildlife - RUTH KANSKY; MARTIN KIDD; ANDREW T. KNIGHT (Conservation Biology, 2014)
Many populations of threatened mammals persist outside formally protected areas, and their survival depends on the willingness of communities to coexist with them. An understanding of the attitudes, and specifically the tolerance, of individuals and communities and the factors that determine these is therefore fundamental to designing strategies to alleviate human‐wildlife conflict. We conducted a meta‐analysis to identify factors that affected attitudes toward 4 groups of terrestrial mammals. Elephants (65%) elicited the most positive attitudes, followed by primates (55%), ungulates (53%), and carnivores (44%). Urban residents presented the most positive attitudes (80%), followed by commercial farmers (51%) and communal farmers (26%). A tolerance to damage index showed that human tolerance of ungulates and primates was proportional to the probability of experiencing damage while elephants elicited tolerance levels higher than anticipated and carnivores elicited tolerance levels lower than anticipated. Contrary to conventional wisdom, experiencing damage was not always the dominant factor determining attitudes. Communal farmers had a lower probability of being positive toward carnivores irrespective of probability of experiencing damage, while commercial farmers and urban residents were more likely to be positive toward carnivores irrespective of damage. Urban residents were more likely to be positive toward ungulates, elephants, and primates when probability of damage was low, but not when it was high. Commercial and communal farmers had a higher probability of being positive toward ungulates, primates, and elephants irrespective of probability of experiencing damage. Taxonomic bias may therefore be important. Identifying the distinct factors explaining these attitudes and the specific contexts in which they operate, inclusive of the species causing damage, will be essential for prioritizing conservation investments. Meta‐Análisis de las Posturas hacia la Mamíferos Silvestres Causantes de Daños

Specificity of Herbivore-Induced Hormonal Signaling and Defensive Traits in Five Closely Related Milkweeds (Asclepias spp.) - Anurag A. Agrawal; Amy P. Hastings; Eamonn T. Patrick; Anna C. Knight (Journal of Chemical Ecology, 2014)

Determination of the safety and efficacy of therapeutic neutralization of tumor necrosis factor-α (TNF-α) using AZD9773, an anti-TNF-α immune Fab, in murine CLP sepsis - Peter Newham; Daniel Ross; Peter Ceuppens; Shampa Das; James W. T. Yates; Catherine Betts; Jaimini Reens; Kevin J. Randall; Richard Knight; Jennifer S. McKay (Inflammation Research, 2014)

Genetic and morphometric differences demonstrate fine‐scale population substructure of the yellow perch Perca flavescens : need for redefined management units - P. M. Kocovsky; T. J. Sullivan; C. T. Knight; C. A. Stepien (Journal of Fish Biology, 2013)
Whole‐body morphometrics and 15 nuclear DNA microsatellite loci were analysed for 158 Perca flavescens collected during the spawning season from four spawning locations in central Lake Erie, two along the northern shore and two along the southern shore, to evaluate fine‐scale variation (spanning 17–94 km). Results showed significant morphological and genetic differences among P. flavescens from the four locations. The magnitudes of differences were unrelated to geographic distance, demonstrating spatially heterogeneous levels of genetic divergence. These results linked morphometric and genetic variation, showing a discontinuity of scale between currently defined management units and population structure of P. flavescens in Lake Erie, and support that P. flavescens might exist as one or more metapopulations. Findings demonstrate the value of using complementary techniques for evaluating population structure.

Diversity, distribution and sources of bacteria in residential kitchens - Gilberto E. Flores; Scott T. Bates; J. Gregory Caporaso; Christian L. Lauber; Jonathan W. Leff; Rob Knight; Noah Fierer (Environmental Microbiology, 2013)
Summary Bacteria readily colonize kitchen surfaces, and the exchange of microbes between humans and the kitchen environment can impact human health. However, we have a limited understanding of the overall diversity of these communities, how they differ across surfaces and sources of bacteria to kitchen surfaces. Here we used high‐throughput sequencing of the 16 S rRNA gene to explore biogeographical patterns of bacteria across > 80 surfaces within the kitchens of each of four households. In total, 34 bacterial and two archaeal phyla were identified, with most sequences belonging to the A ctinobacteria , B acteroidetes , F irmicutes and P roteobacteria . Genera known to contain common food‐borne pathogens were low in abundance but broadly distributed throughout the kitchens, with different taxa exhibiting distinct distribution patterns. The most diverse communities were associated with infrequently cleaned surfaces such as fans above stoves, refrigerator/freezer door seals and floors. In contrast, the least diverse communities were observed in and around sinks, which were dominated by biofilm‐forming G ram‐negative lineages. Community composition was influenced by conditions on individual surfaces, usage patterns and dispersal from source environments. Human skin was the primary source of bacteria across all kitchen surfaces, with contributions from food and faucet water dominating in a few specific locations. This study demonstrates that diverse bacterial communities are widely distributed in residential kitchens and that the composition of these communities is often predictable. These results also illustrate the ease with which human‐ and food‐associated bacteria can be transferred in residential settings to kitchen surfaces.

“This is not an Apple”–Yeast Mutualism in Codling Moth - Peter Witzgall; Magali Proffit; Elzbieta Rozpedowska; Paul G. Becher; Stefanos Andreadis; Miryan Coracini; Tobias U. T. Lindblom; Lee J. Ream; Arne Hagman; Marie Bengtsson; Cletus P. Kurtzman; Jure Piskur; et al. (Journal of Chemical Ecology, 2012)

Population genetic structure and long‐distance dispersal among seabird populations: Implications for colony persistence - A. W. J. BICKNELL; M. E. KNIGHT; D. BILTON; J. B. REID; T. BURKE; S. C. VOTIER (Molecular Ecology, 2012)
Dramatic local population decline brought about by anthropogenic‐driven change is an increasingly common threat to biodiversity. Seabird life history traits make them particularly vulnerable to such change; therefore, understanding population connectivity and dispersal dynamics is vital for successful management. Our study used a 357‐base pair mitochondrial control region locus sequenced for 103 individuals and 18 nuclear microsatellite loci genotyped for 245 individuals to investigate population structure in the Atlantic and Pacific populations of the pelagic seabird, Leach’s storm‐petrel Oceanodroma leucorhoa leucorhoa . This species is under intense predation pressure at one regionally important colony on St Kilda, Scotland, where a disparity between population decline and predation rates hints at immigration from other large colonies. amova , F ST, Φ ST and Bayesian cluster analyses revealed no genetic structure among Atlantic colonies (Global Φ ST = −0.02 P > 0.05, Global F ST = 0.003, P > 0.05, structure K = 1), consistent with either contemporary gene flow or strong historical association within the ocean basin. The Pacific and Atlantic populations are genetically distinct (Global Φ ST = 0.32 P F ST = 0.04, P structure K = 2), but evidence for interocean exchange was found with individual exclusion/assignment and population coalescent analyses. These findings highlight the importance of conserving multiple colonies at a number of different sites and suggest that management of this seabird may be best viewed at an oceanic scale. Moreover, our study provides an illustration of how long‐distance movement may ameliorate the potentially deleterious impacts of localized environmental change, although direct measures of dispersal are still required to better understand this process.

Extracellular 14-3-3 from human lung epithelial cells enhances MMP-1 expression - Negar Asdaghi; Ruhangiz T. Kilani; Azadeh Hosseini-Tabatabaei; Solomon O. Odemuyiwa; Tillie-Louise Hackett; Darryl A. Knight; Aziz Ghahary; Redwan Moqbel (Molecular and Cellular Biochemistry, 2012)

Characterisation and predicted genome locations of Leach’s storm-petrel (Oceanodroma leucorhoa) microsatellite loci (Procellariidae, Aves) - Anthony W. J. Bicknell; Deborah A. Dawson; Gavin J. Horsburgh; Mairi E. Knight; David T. Bilton; Stephen C. Votier (Conservation Genetics Resources, 2011)

What about the People? - Andrew T. Knight (Conservation Biology, 2011)

Clozapine and other competitive antagonists reactivate risperidone-inactivated h5-HT7 receptors: radioligand binding and functional evidence for GPCR homodimer protomer interactions - Milt Teitler; Nicole Toohey; Jessica A. Knight; Michael T. Klein; Carol Smith (Psychopharmacology, 2010)

Climate forcings and climate sensitivities diagnosed from atmospheric global circulation models - Bruce T. Anderson; Jeff R. Knight; Mark A. Ringer; Clara Deser; Adam S. Phillips; Jin-Ho Yoon; Annalisa Cherchi (Climate Dynamics, 2010)

Mapping Human and Social Dimensions of Conservation Opportunity for the Scheduling of Conservation Action on Private Land - ANDREW T. KNIGHT; RICHARD M. COWLING; MARK DIFFORD; BRUCE M. CAMPBELL (Conservation Biology, 2010)
Spatial prioritization techniques are applied in conservation‐planning initiatives to allocate conservation resources. Although typically they are based on ecological data (e.g., species, habitats, ecological processes), increasingly they also include nonecological data, mostly on the vulnerability of valued features and economic costs of implementation. Nevertheless, the effectiveness of conservation actions implemented through conservation‐planning initiatives is a function of the human and social dimensions of social‐ecological systems, such as stakeholders’ willingness and capacity to participate. We assessed human and social factors hypothesized to define opportunities for implementing effective conservation action by individual land managers (those responsible for making day‐to‐day decisions on land use) and mapped these to schedule implementation of a private land conservation program. We surveyed 48 land managers who owned 301 land parcels in the Makana Municipality of the Eastern Cape province in South Africa. Psychometric statistical and cluster analyses were applied to the interview data so as to map human and social factors of conservation opportunity across a landscape of regional conservation importance. Four groups of landowners were identified, in rank order, for a phased implementation process. Furthermore, using psychometric statistical techniques, we reduced the number of interview questions from 165 to 45, which is a preliminary step toward developing surrogates for human and social factors that can be developed rapidly and complemented with measures of conservation value, vulnerability, and economic cost to more‐effectively schedule conservation actions. This work provides conservation and land management professionals direction on where and how implementation of local‐scale conservation should be undertaken to ensure it is feasible.

The importance of coastal sand dunes for terrestrial invertebrates in Wales and the UK, with particular reference to aculeate Hymenoptera (bees, wasps & ants) - M. A. Howe; G. T. Knight; C. Clee (Journal of Coastal Conservation, 2010)

Invest in Opportunity, Not Inventory of Hotspots - RICHARD M. COWLING; ANDREW T. KNIGHT; SEAN D. J. PRIVETT; GYAN SHARMA (Conservation Biology, 2010)

Night sampling improves indices used for management of yellow perch in Lake Erie - P. M. KOCOVSKY; M. A. STAPANIAN; C. T. KNIGHT (Fisheries Management and Ecology, 2010)
Catch rate (catch per hour) was examined for age‐0 and age‐1 yellow perch, Perca flavescens (Mitchill), captured in bottom trawls from 1991 to 2005 in western Lake Erie: (1) to examine variation of catch rate among years, seasons, diel periods and their interactions; and (2) to determine whether sampling during particular diel periods improved the management value of CPH data used in models to project abundance of age‐2 yellow perch. Catch rate varied with year, season and the diel period during which sampling was conducted as well as by the interaction between year and season. Indices of abundance of age‐0 and age‐1 yellow perch estimated from night samples typically produced better fitting models and lower estimates of age‐2 abundance than those using morning or afternoon samples, whereas indices using afternoon samples typically produced less precise and higher estimates of abundance. The diel period during which sampling is conducted will not affect observed population trends but may affect estimates of abundance of age‐0 and age‐1 yellow perch, which in turn affect recommended allowable harvest. A field experiment throughout western Lake Erie is recommended to examine potential benefits of night sampling to management of yellow perch.

The CLIVAR C20C project: which components of the Asian–Australian monsoon circulation variations are forced and reproducible? - Tianjun Zhou; Bo Wu; A. A. Scaife; S. Brönnimann; A. Cherchi; D. Fereday; A. M. Fischer; C. K. Folland; K. E. Jin; J. Kinter; J. R. Knight; F. Kucharski; et al. (Climate Dynamics, 2009)

Effects of an Atrazine, Metolachlor and Fipronil Mixture on Hyalella azteca (Saussure) in a Modified Backwater Wetland - Richard E. Lizotte; Scott S. Knight; F. Douglas Shields; Charles T. Bryant (Bulletin of Environmental Contamination and Toxicology, 2009)

The CLIVAR C20C project: skill of simulating Indian monsoon rainfall on interannual to decadal timescales. Does GHG forcing play a role? - F. Kucharski; A. A. Scaife; J. H. Yoo; C. K. Folland; J. Kinter; J. Knight; D. Fereday; A. M. Fischer; E. K. Jin; J. Kröger; N.-C. Lau; T. Nakaegawa; et al. (Climate Dynamics, 2009)

The CLIVAR C20C project: selected twentieth century climate events - A. A. Scaife; F. Kucharski; C. K. Folland; J. Kinter; S. Brönnimann; D. Fereday; A. M. Fischer; S. Grainger; E. K. Jin; I. S. Kang; J. R. Knight; S. Kusunoki; et al. (Climate Dynamics, 2009)

Agricultural Pesticides in Mississippi Delta Oxbow Lake Sediments During Autumn and Their Effects on Hyalella azteca - Richard E. Lizotte; Scott S. Knight; Charles T. Bryant; Sammie Smith (Archives of Environmental Contamination and Toxicology, 2009)

Ipsilesional trajectory control is related to contralesional arm paralysis after left hemisphere damage - Kathleen Y. Haaland; Sydney Y. Schaefer; Robert T. Knight; John Adair; Alvaro Magalhaes; Joseph Sadek; Robert L. Sainburg (Experimental Brain Research, 2009)

Is Conservation Biology Ready to Fail? - Andrew T. Knight (Conservation Biology, 2009)

Mississippi Oxbow Lake Sediment Quality During an Artificial Flood - S. S. Knight; R. E. Lizotte; M. T. Moore; S. Smith; F. D. Shields (Bulletin of Environmental Contamination and Toxicology, 2009)

Clearing the Mud from the Conservation Opportunity Debate: Reply to Pressey and Bottrill - ANDREW T. KNIGHT; RICHARD M. COWLING (Conservation Biology, 2008)

Knowing But Not Doing: Selecting Priority Conservation Areas and the Research–Implementation Gap - ANDREW T. KNIGHT; RICHARD M. COWLING; MATHIEU ROUGET; ANDREW BALMFORD; AMANDA T. LOMBARD; BRUCE M. CAMPBELL (Conservation Biology, 2008)
Conservation assessment is a rapidly evolving discipline whose stated goal is the design of networks of protected areas that represent and ensure the persistence of nature (i.e., species, habitats, and environmental processes) by separating priority areas from the activities that degrade or destroy them. Nevertheless, despite a burgeoning scientific literature that ever refines these techniques for allocating conservation resources, it is widely believed that conservation assessments are rarely translated into actions that actually conserve nature. We reviewed the conservation assessment literature in peer‐reviewed journals and conducted survey questionnaires of the authors of these studies. Two‐thirds of conservation assessments published in the peer‐reviewed scientific literature do not deliver conservation action, primarily because most researchers never plan for implementation. This research–implementation gap between conservation science and real‐world action is a genuine phenomenon and is a specific example of the “knowing–doing gap” that is widely recognized in management science. Given the woefully inadequate resources allocated for conservation, our findings raise questions over the utility of conservation assessment science, as currently practiced, to provide useful, pragmatic solutions to conservation planning problems. A reevaluation of the conceptual and operational basis of conservation planning research is urgently required. We recommend the following actions for beginning a process for bridging the research–implementation gap in conservation planning: (1) acknowledge the research–implementation gap is real, (2) source research questions from practitioners, (3) situate research within a broader conservation planning model, (4) expand the social dimension of conservation assessments, (5) support conservation plans with transdisciplinary social learning institutions, (6) reward academics for societal engagement and implementation, and (7) train students in skills for “doing” conservation.

Management of ascochyta blight in chickpeas in Australia - T. W. Bretag; W. J. MacLeod; R. B. E. Kimber; K. J. Moore; E. J. C. Knights; J. A. Davidson (Australasian Plant Pathology, 2008)

Reproductive biology of the endangered Oxleyan pygmy perch Nannoperca oxleyana Whitley - J. T. Knight; G. L. Butler; P. S. Smith; R. N. E. Wager (Journal of Fish Biology, 2007)
The reproductive biology of the Oxleyan pygmy perch Nannoperca oxleyana is described from simultaneous studies of wild populations in north‐eastern New South Wales and mature fish held in aquaria. In the wild, 50% of males and females matured at total lengths of 24·0–25·9 and 28·0–29·9 mm, respectively. The species displays sexual dichromatism during the spawning season, with males developing more intense red and brown fin and body colouration, and black pelvic fins. Captive male broodfish displayed territoriality during the breeding season, closely guarding sites within artificial, plant‐like substrata in which pairs of fish spawned adhesive eggs. Protracted serial spawning of wild and captive fish occurred from September to April and May at mean water temperatures ≥16·6° C and day length ≥10·7 h. Captive broodfish spawned on an average of 57% of days during the 256 day spawning period. Gonado‐somatic indices averaged 0·7% for all ripe males and 4·1–4·2% for all ripe females collected. Mean total and batch fecundities of captive females were 1323 eggs per fish and 7·8 eggs per fish per day, respectively, and relative fecundity was 587 eggs g −1 of body mass. Batch fecundity of wild females was estimated at 7·8 eggs per fish. The adaptive significance of this reproductive strategy in a harsh, variable environment is discussed.

Diazinon Mitigation in Constructed Wetlands: Influence of Vegetation - M. T. Moore; C. M. Cooper; S. Smith; R. F. Cullum; S. S. Knight; M. A. Locke; E. R. Bennett (Water, Air, & Soil Pollution, 2007)

Embracing Opportunism in the Selection of Priority Conservation Areas - ANDREW T. KNIGHT; RICHARD M. COWLING (Conservation Biology, 2007)

Sensitivity Analysis of Aggregated Indices for Integrated Assessment with a Case Study of the Mid-Atlantic Region - Liem T. Tran; Robert V. O’Neill; Elizabeth R. Smith; C. Gregory Knight (Environmental Management, 2007)

Failing but Learning: Writing the Wrongs after Redford and Taber - ANDREW T. KNIGHT (Conservation Biology, 2006)

Tidal circulation in Tasman and Golden Bays: Implications for river plume behaviour - Benjamin J. Tuckey; Mark T. Gibbs; Benjamin R. Knight; Paul A. Gillespie (New Zealand Journal of Marine and Freshwater Research, 2006)
An investigation into the tidal residual circulation in the Tasman/Golden Bays system was performed. This investigation involved collecting hydrographic and current meter data, and configuring a numerical circulation model. The model was able to reproduce the gross features of the major tidal flows within the system revealed by the data. The simulated tidal residual circulation conformed to that previously suggested, except along the western side of Tasman Bay where this investigation suggests that residual flows move northwards. The validated model was then used to produce simulations of the fate of the plumes from the major rivers. Salinity field simulations describing different river flow and wind direction/velocity scenarios suggest that the Motueka River plume can cover considerable proportions of western side Tasman Bay, extending into Golden Bay during flood conditions. The embedded sediment transport model was also used to investigate the fate of fine sediments entering the bays. Simulated distribution patterns of fine sediments entering the bays from the four major tributaries were found to be consistent with existing bathymetric and seabed substrate characteristics.

Designing Systematic Conservation Assessments that Promote Effective Implementation: Best Practice from South Africa - ANDREW T. KNIGHT; AMANDA DRIVER; RICHARD M. COWLING; KRISTAL MAZE; PHILIP G. DESMET; AMANDA T. LOMBARD; MATHIEU ROUGET; MARK A. BOTHA; ANDRE F. BOSHOFF; J. GUY CASTLEY; PETER S. GOODMAN; KATHY MACKINNON; et al. (Conservation Biology, 2006)
Systematic conservation assessment and conservation planning are two distinct fields of conservation science often confused as one and the same. Systematic conservation assessment is the technical, often computer‐based, identification of priority areas for conservation. Conservation planning is composed of a systematic conservation assessment coupled with processes for development of an implementation strategy and stakeholder collaboration. The peer‐reviewed conservation biology literature abounds with studies analyzing the performance of assessments (e.g., area‐selection techniques). This information alone, however, can never deliver effective conservation action; it informs conservation planning. Examples of how to translate systematic assessment outputs into knowledge and then use them for “doing” conservation are rare. South Africa has received generous international and domestic funding for regional conservation planning since the mid‐1990s. We reviewed eight South African conservation planning processes and identified key ingredients of best practice for undertaking systematic conservation assessments in a way that facilitates implementing conservation action. These key ingredients include the design of conservation planning processes, skills for conservation assessment teams, collaboration with stakeholders, and interpretation and mainstreaming of products (e.g., maps) for stakeholders. Social learning institutions are critical to the successful operationalization of assessments within broader conservation planning processes and should include not only conservation planners but also diverse interest groups, including rural landowners, politicians, and government employees.

An Operational Model for Implementing Conservation Action - ANDREW T. KNIGHT; RICHARD M. COWLING; BRUCE M. CAMPBELL (Conservation Biology, 2006)
The preoccupation of many conservation planners with the refinement of systematic assessment techniques has manifested an “implementation crisis” in conservation planning. This preoccupation has provided systematic assessments with well‐tested tools (e.g., area selection algorithms) and principles (e.g., representation, complementarity), but our understanding of these techniques currently far exceeds our ability to apply them effectively to pragmatic conservation problems. The science is informative about where one needs to do conservation, but silent on how to achieve it. Operational models, defined as simplified conceptualizations of processes for implementing conservation action at priority conservation areas, are essential for guiding conservation planning initiatives because they assist understanding of how these processes function. Operational models developed to date have largely been linear, simplistic, and focused on the systematic assessment of biological entities. Experience in the real world indicates that operational models for conducting conservation planning initiatives should explicitly complement a systematic conservation assessment with activities that empower individuals and institutions (enabling) and explicitly aim to secure conservation action (implementation). Specifically, implementing effective conservation action requires that systematic assessments be integrated functionally with a process for developing an implementation strategy and processes for stakeholder collaboration while maintaining a broad focus on the implementation of conservation action. A suite of hallmarks define effective operational models (e.g., stakeholder collaboration, links with land‐use planning, social learning, and action research). Greater development and testing of the practical application of operational models should lead to higher levels of effective implementation and alleviate the implementation crisis. Social learning institutions are essential for ensuring ongoing improvement in the development and application of operational models that deliver effective conservation action.

Designing Large‐Scale Conservation Corridors for Pattern and Process - MATHIEU ROUGET; RICHARD M. COWLING; AMANDA T. LOMBARD; ANDREW T. KNIGHT; GRAHAM I.H. KERLEY (Conservation Biology, 2006)
A major challenge for conservation assessments is to identify priority areas that incorporate biological patterns and processes. Because large‐scale processes are mostly oriented along environmental gradients, we propose to accommodate them by designing regional‐scale corridors to capture these gradients. Based on systematic conservation planning principles such as representation and persistence, we identified large tracts of untransformed land (i.e., conservation corridors) for conservation that would achieve biodiversity targets for pattern and process in the Subtropical Thicket Biome of South Africa. We combined least‐cost path analysis with a target‐driven algorithm to identify the best option for capturing key environmental gradients while considering biodiversity targets and conservation opportunities and constraints. We identified seven conservation corridors on the basis of subtropical thicket representation, habitat transformation and degradation, wildlife suitability, irreplaceability of vegetation types, protected area networks, and future land‐use pressures. These conservation corridors covered 21.1% of the planning region (ranging from 600 to 5200 km 2 ) and successfully achieved targets for biological processes and to a lesser extent for vegetation types. The corridors we identified are intended to promote the persistence of ecological processes (gradients and fixed processes) and fulfill half of the biodiversity pattern target. We compared the conservation corridors with a simplified corridor design consisting of a fixed‐width buffer along major rivers. Conservation corridors outperformed river buffers in seven out of eight criteria. Our corridor design can provide a tool for quantifying trade‐offs between various criteria (biodiversity pattern and process, implementation constraints and opportunities). A land‐use management model was developed to facilitate implementation of conservation actions within these corridors.

Nature Conservation Requires More than a Passion for Species - RICHARD M. COWLING; ANDREW T. KNIGHT; DANIEL P. FAITH; SIMON FERRIER; AMANDA T. LOMBARD; AMANDA DRIVER; MATHIEU ROUGET; KRISTAL MAZE; PHILIP G. DESMET (Conservation Biology, 2004)

Integrated Environmental Assessment of the Mid-Atlantic Region with Analytical Network Process - Liem T. Tran; C. Gregory Knight; Robert V. O'Neill; Elizabeth R. Smith (Environmental Monitoring and Assessment, 2004)

Survival and Growth of Hyalella azteca Exposed to Three Mississippi Oxbow Lake Sediments - M. T. Moore; R. E. Lizotte; C. M. Cooper; S. Smith; S. S. Knight (Bulletin of Environmental Contamination and Toxicology, 2004)

Construction and integration of radiation-hybrid and cytogenetic maps of dog Chromosome X - Helen F. Spriggs; Nigel G. Holmes; Matthew Breen; Panos Deloukas; Cordelia F. Langford; Mark T. Ross; Nigel P. Carter; Maria E. Davis; Catherine Knights; Angela Smith; Christine J. Farr; Linda C. McCarthy; et al. (Mammalian Genome, 2003)

Fuzzy Decision Analysis for Integrated Environmental Vulnerability Assessment of the Mid-Atlantic Region 1 - Liem T. Tran; C. Gregory Knight; Robert V. O'Neill; Elizabeth R. Smith; Kurt H. Riitters; James Wickham (Environmental Management, 2002)

Sulphation of the salivary mucin MG1 (MUC-5B) is not correlated to the degree of its sialylation and is unaffected by cystic fibrosis - Shori D.; Hansen J.; Kalogeridis A.; Kariyawasam H.; Genter T.; Koch C.; Knight R.; Hodson M. (Pflügers Archiv - European Journal of Physiology, 2001)

Altered sialyl- and fucosyl-linkage on mucins in cystic fibrosis patients promotes formation of the sialyl-Lewis X determinant on salivary MUC-5B and MUC-7 - Shori D.; Genter T.; Hansen J.; Koch C.; Wyatt H.; Kariyawasam H.; Knight R.; Hodson M.; Kalogeridis A.; Tsanakas I. (Pflügers Archiv - European Journal of Physiology, 2001)

Octahedral cation ordering in olivine at high temperature. II: an in situ neutron powder diffraction study on synthetic MgFeSiO 4 (Fa50) - S. A. T. Redfern; G. Artioli; R. Rinaldi; C. M. B. Henderson; K. S. Knight; B. J. Wood (Physics and Chemistry of Minerals, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Long-term effects of elevated CO 2 and temperature on populations of the peach potato aphid Myzus persicae and its parasitoid Aphidius matricariae - T. Martijn Bezemer; T. Hefin Jones; Kevin J. Knight (Oecologia, 1998)